The German Lutheran Church and the Rise of National Socialism - Tiefel, Hans (Church history, 1972)
The attempt to arrive at a balanced and objective understanding of the relationship between the German Protestant church, which is predominantly Lutheran, and the rise of National Socialism is an almost impossible task today. For what we now hear about the Protestant church of the thirties tends to be written by those who were vindicated by the turn of events, while those who supported Hitler and National Socialism have tended to remain silent, understandably enough. The flood of books and articles by the Confessing Church gives the misleading impression that the stand of the church toward the Nazi state was one of resistance and opposition. Instead, the main Protestant response to Hitler and to the nationalistic forces he represented ranged from inactive indifference to over-whelming support. The Confessing Church, which did display a courageous though not always consistent opposition, at best never spoke for more than about one tenth of all Protestant Christians.